Strategi Promosi Syariah Dalam Meningkatkan Penjualan Produk : (Studi Pada UMKM ARS Snack Kota Jambi) - Ari Lesmana; Ahsan Putra Hafiz; Aztyara Ismadharliani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to determine sharia promotional strategies, inhibiting factors and efforts to increase sales of ars snack msmes in jambi city. This research uses qualitative methods. This research is the owner of the msme ars snack. Data collection through observation, interviews and documentation. the conclusion results show that: the sharia promotion strategy carried out by msme ars has implemented the fathonah characteristic, namely being smart in innovating to update and add to its products. Maintaining and improving the quality of its products so as to create customer trust in ars snack msmes by always paying attention to sharia regulations. Advertisements carried out by ars snack msmes have implemented the characteristics of siddiq and trust both on social media and in brochures and must still prioritize honesty, truth and trustworthiness based on islamic economic perspective, personal sales carried out by umkm ars snack apply tabliq characteristics, namely meeting directly with customers and potential customers by conveying correctly using appropriate and easy to understand words without cheating about the products being sold. The public relations owned by msme ars snack jambi city is specifically to build good relationships with various groups, build a good company image and support each other among msmes and promote products to increase sales of each msme player.